Challenges Faced by Public Libraries in Delivering Services to Users: A Case Study of Kigali Public Library. - Rachel, Mukabarisa (Kabale University, 2019)
A Research Report Submitted to the Faculty of Arts and Social Sciences in Partial Fulfillment of the Requirement for the award of a Degree in Library and Information Science of Kabale University